AN INVESTIGATION INTO TIME EXPRESSIONS RELATING TO SPACE IN ENGLISH AND VIETNAMESE - TRẦN THỊ LAN PHƯƠNG (2015)
This thesis takes as its main objective the description of prepositions relating to space and time in terms of the syntactic and semantic features in English and Vietnamese. In this original study, the thesis discusses the use of prepositions in English, through examining examples found in various linguistic books, textbooks, English short stories, newspapers and from the Internet. Prepositional elements that typically refer to circumstances of time, space, cover a range of meanings and can be placed at the beginning, in the middle or at the end of a sentence. The description of the frequency of meaning types and discussion of the reasons for selecting positions show that the use of prepositions differs across text types. Prepositional usage is often linked to the general build-up of a text and can reflect its content and purpose. In using real texts, this paper identifies a challenge for the classification of prepositions, and also highlights the fact that some prepositions have uses temporal expressions are based on spatial ones. Also, the paper is then focused on discover and contrast these prepositions to its Vietnamese equivalents to enhance the effectiveness of teaching, learning and translating as well as further studying these kinds of prepositions